2018
DOI: 10.1302/0301-620x.100b3.bjj-2017-0863.r1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and functional outcomes of complex tibial fractures in children and adolescents using the Ilizarov method

Abstract: The Ilizarov method is a safe, effective and reliable method for the treatment of complex paediatric tibial fractures. Cite this article: Bone Joint J 2018;100-B:396-403.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…For this reason, we decided to not consider it among the sequelae recorded at long follow-up. Messner et al reported that Ilizarov is a safe, effective, and reliable method for the treatment of tibial fractures with good but short-term outcomes [21]. Other studies have compared the complication rate of external fixation devices and highlighted possible solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, we decided to not consider it among the sequelae recorded at long follow-up. Messner et al reported that Ilizarov is a safe, effective, and reliable method for the treatment of tibial fractures with good but short-term outcomes [21]. Other studies have compared the complication rate of external fixation devices and highlighted possible solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, during the follow-up period, we could not evaluate 74 patients (50.7%) because of two main reasons: they could not be contacted by telephone (having moved), or they had died. Therefore, 72 among 146 (49.3%) were retrospectively enrolled in the present study; no one was lost up to the average final clinical follow-up of 21 was the most represented with 46 cases (82%), bicycle accidents in 6 cases (11%) and 4 cases (7%) of falls from height. In the DG, there were 16 patients treated, 6 cases for post-traumatic tibial deformities, 4 cases for valgus knees, 4 cases for hypometric tibias (Fig.…”
Section: Patients' Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Of the excluded full texts, the most common reason for exclusion was that open fractures could not be separated (10 studies) [19][20][21][22][23][24][25][26][27][28] followed by studies with too small population (7 studies). [29][30][31][32][33][34][35] In two studies, 36,37 distal tibia fractures were no distinguishable from diaphyseal fractures, and two studies 38,39 reported only the incidence of compartment syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Available evidence would suggest that Ilizarov management is safe, effective and well tolerated in children with tibial fractures. 12 , 13 …”
Section: Onclusionmentioning
confidence: 99%